A century of leadership : biographies of Kappa Delta Pi presidents - Davis, O. L. 1928-; Spearman, Mindy (Research in curriculum and instruction., 2011)
Kappa Delta Pi is an international honor society in Education founded in 1911. This book chronicles the leadership of Kappa Delta Pi across the past century through a collection of short life stories about the 32 individuals who were elected by members to lead the Society. Through their work with their fellow officers, they helped keep alive the flame that called attention to the importance of highly qualified teachers in American schools, in the main, teachers whose academic credentials were very strong.These life stories attend to KDP presidents' contributions to education, particularly with emphasis a) on high academic scholarship for educational professionals, e.g., teacher candidates, teachers at all levels, school administrators, college and university faculty members in education and in fields related to educational practice and knowledge; b) toward teacher candidates' mindful learning in and the integration of liberal arts, education, and other fields of study; c) and in the support and fostering of scholarly endeavors, especially substantive research and creative developments in the educational processes of schooling - all or many related to the individual's involvement in Kappa Delta Pi.A number of elements of Kappa Delta Pi's purposes and practices during its first century are illuminated in this book. Many others remain obscured, neglected, or unknown. Readers reasonably may discover keys to increased understanding and wonderment as they read and think about the lives of these former presidents, particularly about their contributions to the continuance and strengthening of the Society. One impressive key surely is evident. Their presidencies not only helped Kappa Delta Pi to continue to exist. They also fostered the fruitful creation of this honor society in education. And so also will those members and leaders who, succeeding these former presidents, enter confidently into Kappa Delta Pi's second century.